Propagação in vitro de orquídeas Phalaenopsis por segmentos de inflorescências e embriogênese somática - Zanello, Cesar Augusto (2018)
The orchids of the genus Phalaenopsis are the most important in the segment of potted flowers in the national floriculture, being currently leader in volume of production and commercialization. However, obtaining genetic and phytosanitary quality seedlings at a competitive price has been one of the main obstacles for producers. Thus, the establishment of protocols of commercial applicability and that aim the production of clonal seedlings of hybrids is of great interest for the self-sufficiency of this sector. For this, micropropagation, through the production of somatic embryos (PLBs) or adventitious buds in somatic tissue segments in vitro, may be a viable alternative for the production of Phalaenopsis seedlings. This work aimed to establish efficient micropropagation protocols for Phalaenopsis hybrids using shoot induction techniques in inflorescence segments and induction and regeneration of somatic embryos (PLBs) in vitro from leaf segments of commercial hybrids. Based on the results, it was concluded that the use of the NDM culture medium plus 0.1 g L-1 inositol, 20 g L-1 sucrose, 0.1 mg L-1 NAA, 1.0 mg L-1 of BA, 1.5 mg L-1 of GA3, pH 5.7, is the most suitable for propagation of Phalaenopsis using inflorescence segments in the induction of shoots in vitro, being able to generate up to 1.7 shoots / segment and 71.5% of living segments. The contamination of the segments of inflorescence by yeast was the main difficulty found, reaching an average of 30% of contaminated segments. As for the induction of PLBs from leaf segments, the use of plant regulators BA and TDZ at a concentration of 1.5 mg L-1 each was beneficial for the regeneration of PLBs, whereas the different salt formulations used (MS and NDM) had little influence. The best results were 41% of regenerating segments and up to 5.3 PLBs / segment with the use of leaves with 20 days of subcultivation segmented in Thin Cell Layer. Under the culture conditions evaluated, it was not possible to obtain embryos using as explant segments of young leaves collected from plants under greenhouse conditions. According to the results, it was possible to prove the influence of the genotype factor on the induction and regeneration of PLBs.